Determine The Optimum Loan Portfolio Of Commercial Banks Using Quadratic Programming - محمد , رامي (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This research aims to determine the optimal loans portfolio of private commercial banks in Syria during the period (2007- 2015), depending on the quadratic programming method and compare it with the Actual loan portfolio of these banks in terms of (rate of return - the degree of risk and the coefficient of variation). The research concludes to: Optimal loan portfolio achieved a rate of return (11.140%) which is higher than the real yield of the loan portfolio rate (11.07%) of the Syrian Commercial Banks' own place of study. It achieved the optimum degree of risk of the loan portfolio (2.097%) which is less than the degree of risk (3.858%) real Syrian loans to commercial banks own portfolio under study. Optimal loan portfolio achieved a variation coefficient (0.188) which is less than the coefficient of variation (0348) for the portfolio of real loans and the Syrian Commercial Banks' own place of study.